2021
DOI: 10.1002/ece3.7287
|View full text |Cite
|
Sign up to set email alerts
|

Trait means or variance—What determines plant species' local and regional occurrence in fragmented dry grasslands?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Prior research from tallgrass prairies shows high LDMC may likewise affect species' abundance across much of the central plains of North America; at sites in Minnesota and Kansas, the most abundant species tended to have higher tissue density in their leaves and roots (Craine et al ., 2001; Craine & Towne, 2010; Tucker et al ., 2011). Similarly, a study focusing on ‘dry’ grasslands in Germany found that more abundant species had higher LDMC (Bergholz et al ., 2021). By contrast, for a compilation of grasslands in Germany that are more mesic, nutrient‐rich and typically mowed, abundant species tended to have roots with low density and/or thin diameter (Lachaise et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research from tallgrass prairies shows high LDMC may likewise affect species' abundance across much of the central plains of North America; at sites in Minnesota and Kansas, the most abundant species tended to have higher tissue density in their leaves and roots (Craine et al ., 2001; Craine & Towne, 2010; Tucker et al ., 2011). Similarly, a study focusing on ‘dry’ grasslands in Germany found that more abundant species had higher LDMC (Bergholz et al ., 2021). By contrast, for a compilation of grasslands in Germany that are more mesic, nutrient‐rich and typically mowed, abundant species tended to have roots with low density and/or thin diameter (Lachaise et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Among the traits, ITV Leaf and TD Height better explained occupancy than ITV SUM or TD SUM , respectively. Evidence for the choice of traits affecting importance of trait metrics in explaining occupancy exists in the study from a grassland ecosystem by Bergholz et al (2021). However, their finding of ITV Height being more important than ITV Leaf is opposite to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, common plant species typically have deeper root systems, particularly in grasslands dominated by herbaceous species compared to most rare species (Li, Zhang, et al, 2011). In ecosystems such as dense grasslands where light competition is intensive, common plant species are usually taller and larger than locally rare species (e.g., Bergholz et al, 2021; Li, Zhang, et al, 2011; Sun et al, 2010; Wei & Wu, 2021), which allows them to achieve larger aboveground and belowground biomass in these communities. Consequently, the deeper roots of the most common species may escape damage by root feeders.…”
Section: Introductionmentioning
confidence: 99%